2003
DOI: 10.1002/bjs.4161
|View full text |Cite
|
Sign up to set email alerts
|

Detection of disseminated tumour cells in blood and bone marrow samples of patients undergoing hepatic resection for metastasis of colorectal cancer

Abstract: Although the number of patients in this study is limited, the presence of disseminated tumour cells did not predict subsequent extrahepatic recurrence. The results strongly suggest that the presence of circulating tumour cells in peripheral blood may reflect transient shedding of tumour cells related to large tumour volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
2
15
2
3
Order By: Relevance
“…Whether these cells are responsible for a later relapse must be determined since no differences could be obtained when the detection rate of CK + cells in the survivor group was compared with those patients who died. Similar conclusions were demonstrated by Velms et al, who showed no correlation between CK-20 positivity in blood or bone marrow and later extrahepatic tumor recurrence (26).…”
Section: Discussionsupporting
confidence: 89%
“…Whether these cells are responsible for a later relapse must be determined since no differences could be obtained when the detection rate of CK + cells in the survivor group was compared with those patients who died. Similar conclusions were demonstrated by Velms et al, who showed no correlation between CK-20 positivity in blood or bone marrow and later extrahepatic tumor recurrence (26).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, recurrence may also develop from circulating tumour cells that are shed into the circulation during surgery [7,8] . In the past decades, many prognostic factors of recurrence and survival after hepatectomy for metastatic colorectal cancer have been documented, including both preoperative [9,10] and peri-operative variables [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…mRNA based studies frequently use the same markers and, in addition, guanylcyclase, which is expressed at the apical brush border of colonic cells [14][15][16][17]. To increase the sensitivity and to avoid false positive results, it has been proposed that multiple markers should be used simultaneously [14,[18][19][20][21]. Screening studies for disseminated colorectal cancer cells in the liver based on aberrant DNA have also been used and they mostly evaluate point mutations of K-ras and p53 and fragment length polymorphism.…”
Section: Colorectal Cancer and Metastasismentioning
confidence: 98%